Види і функції ймовірного прогнозування - Брушневська, Ірина Миколаївна; Brushnevska, Iryna M. (Кам’янець-Подільський національний університет імені Івана Огієнка, 2015)
В статті автор аналізує вивчення можливостей використання операцій ймовірного прогнозування у роботі з дітьми дошкільного віку, аргументує доцільність їх застосування у різних видах роботи. Розглядає основні види та функції антиципації, обґрунтовує доречність та результативність застосування її різновидів на різних етапах навчальної діяльності. The author analyzes study of the opportunities of the usage of the operations of the probable prognostication working with preschool children, argues reasonability of their application in different activities. In preschool age the anticipation skills which are an inseparable part of the language activity of a child, are formed very intensely. Distinct recognition by the pedagogues of the basic types and functions of the probable prognostication operations will guarantee succession and system of its application in the pedagogical process. This will favour development of the psychological processes of the preschool child, logical thinking and social and moral competence
Types and functions of theprobable prognostication
Keywords: ймовірне прогнозування; дошкільники; мовлення; досвід; пам’ять; функції; probable prognostication; preschool children; speech; experience; memory; functions